BURUNG HANTU DALAM KARYA JAHIT PERCA DAN SULAMAN - Astri Aprilia, Drs. Erwin A, M.Sn., Drs. Ariusmedi, M.Sn. (Universitas Negeri Padang, 2018)
This final work aims to visualize the beauty and uniqueness of the Owl in the Work of Patchwork and Embroidery. Owls are flesh-eating birds (carnivores), have large, ordinary, hunts in the night's darkness. The method of creating this final paper uses five stages: preparation, elaboration, synthesis, and concept realization begins sketching, sketching, material and tool preparation, work and finishing process. The final stage is the completion to the exhibition. After a long series of creation processes, 7 pieces of work are created, including: 1) Out of the Nest, 2) Dashing, 3) Contemplating, 4) Stare, 5) Silence, 6) Pounce on, 7) Hiding.Kata Kunci : Burung Hantu, Jahit Perca, Sulaman